Soil aggregate structure, stability, and stoichiometric characteristics in a smelter-impacted soil under phytoremediation - Xu, Lei; Xing, Xiangyu; Bai, Jingfeng; Li, Ding (Frontiers in Environmental Science, 2022)
Smelter-impacted soils often result in soil degradation and destroying the soil structure. Typically, soil aggregate plays a crucial role in soil structure, however, how the influence of phytoremediation on soil aggregate structure stability and stoichiometric characteristics is remain unclear. To study the influence of phytoremediation on soil aggregate structure, stability and stoichiometric characteristics, a 3-year in-situ experiment was conducted. After hydroxyapatite was applied, Elsholtzia splendens, Sedum plumbizincicola and Pennisetum sp. were planted in a smelter-impacted soil. After three years, the soil aggregate structure, stability, and stoichiometric of chemical elements were analyzed. The results showed that the 3 phytoremediation treatments increased the content of >0.25 mm mechanical-stable (DR0.25) and water-stable (WR0.25) aggregates by 6.6% - 10.4% and 13.3% - 17.5%, respectively. Aggregate mean weight diameter (MWD), geometric mean diameter (GMD), aggregate stability rate (AR, %) were significantly increased and the soil mechanical-stable aggregate fractal dimension (D) was significantly reduced after 3 years remediation. Soil total nitrogen and phosphorus in aggregates with different particle sizes were significantly increased by 11.4% - 46.4% and 107% - 236% after different plant treatments. For the stoichiometric characteristics of aggregates, the combined remediation only significantly reduced the value of N:P and C:P in different particle size aggregates, but had no significant effect on the C:N in all particle size aggregates. Meanwhile, the combined remediation of hydroxyapatite and Elsholtzia splendens, Sedum plumbizincicola, Pennisetum sp. in heavy metal heavily contaminated soil could reduce the availability of Cu and Cd by 54.1%-72.3% and 20.3%-47.2% during the three years, respectively. In summary, This combined remediation method can be used for the remediation of farmland heavily contaminated by heavy metals.